Results of a randomized controlled trial analyzing telemedically supported case management in the first year after living donor kidney transplantation: A budget impact analysis from the healthcare perspective - Klaus Kaier; Silvia Hils; Stefan Fetzer; Philip Hehn; Anja Schmid; Dieter Hauschke; Lioudmila Bogatyreva; Bernd Jänigen; Przemyslaw Pisarski (Health Economics Review, 2017)
We analyze one-year costs and savings of a telemedically supported case management program after kidney transplantation from the perspective of the German Healthcare System. Recipients of living donor kidney transplantation (N = 46) were randomly allocated to either (1) standard aftercare or (2) standard aftercare plus additional telemedically supported case management. A range of cost figures of each patient's medical service utilization were calculated at month 3, 6 and 12 and analyzed using two-part regression models. In comparison to standard aftercare, patients receiving telemedically supported case management are associated with substantial lower costs related to unscheduled hospitalizations (mean difference: exteuro3,417.46 per patient for the entire one-year period, p = 0.003). Taking all cost figures into account, patients receiving standard aftercare are associated, on average, with one-year medical service utilization costs of exteuro10,449.28, while patients receiving telemedically supported case management are associated with exteuro5,504.21 of costs (mean difference: exteuro 4,945.07 per patient, p < 0.001). With estimated expenditures of exteuro3,001.5 for telemedically supported case management of a single patient, we determined a mean difference of exteuro1,943.57, but this result is not statistically significant (p = 0.128). Sensitivity analyses show that the program becomes cost-neutral at around ten participating patients, and was beneficial starting at 15 patients. Routine implementation of telemedically supported case management in German medium and high-volume transplant centers would result in annual cost savings of exteuro791,033 for the German healthcare system. Patients with telemedically supported case management showed a lower utilization of medical services as well as better medical outcomes. Therefore, such programs should be implemented in medium and high-volume transplant centers.
Keywords: 330; Telemedicine; Cost-of-illness; Cost-benefit